JUDICIAL CONSIDERATIONS ON THE PROTECTION OF WIVES’ AND CHILDREN’S RIGHTS IN ISLAMIC FAMILY LAW AFTER DIVORCE - Engkos Saeful Kholiq; Bambang Hartono (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Divorce in Islamic family law not only terminates the marital relationship but also gives rise to legal consequences concerning the fulfillment of the rights of wives and children after divorce. Therefore, judicial considerations play a strategic role in realizing justice, legal certainty, and legal utility. This thesis aims to analyze judges’ considerations in providing protection for the rights of wives and children after divorce in Decision Number 1127/Pdt.G/2024/PA.Tgm by using the perspectives of justice theory and maqāṣid al-sharīʿah. This research employs a normative juridical method with a case study approach supported by empirical data obtained through interviews and documentation. The data sources consist of primary, secondary, and tertiary legal materials collected through library research and field research, which are then analyzed using descriptive qualitative methods. The results show that the judges’ considerations in the decision are not only based on positive legal provisions such as Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law, but also reflect the principles of distributive justice in the proportional distribution of the rights of wives and children, as well as corrective justice in restoring losses arising from the dissolution of marriage. From the perspective of maqāṣid al-sharīʿah, the protection of rights to maintenance, ḥaḍānah, mutʿah, and child care is directed toward safeguarding religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). The implementation of the decision still encounters obstacles in terms of evidentiary issues, the compliance of the parties, and the effectiveness of enforcement. Therefore, it is necessary to optimize the role of judges in exploring substantive justice and the objectives of Islamic law so that the protection of the rights of wives and children after divorce can be effectively realized in the practice of the Religious Courts. Keywords: Judicial Considerations; Distributive and Corrective Justice; Maqāṣid Al Sharīʿah; Rights of Wives and Children; Islamic Family Law